Study of the Palembang City Watershed Sub-Flood System's Management Priority Scale - Joni Rahalsyah Putra; Anis Saggaff; Arie Setiadi Moerwanto; Kiagus Muhammad Aminuddin (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2023)
A complete watershed management solution and logical outcome is a watershed approach that takes into account watershed capabilities, such as environmental services in the fields of water management and flood prevention. With integrated planning and environmentally responsible, policy-based drainage, floods can be overcome. For spectators and scholars, the topic of flooding has long been of interest as they try to understand its causes and effects. According to studies done by earlier researchers, the city of Palembang has recently been particularly vulnerable to floods, thus it is important to investigate the priority scale of flood control examined for all states in the Palembang city water catchment area. Surveys, field observations, measurements, and documentation are used as the main collecting tools, whilst study location maps are used for secondary data. The SWOT analysis method of scoring is used in the city of Palembang's priority analysis of flood management. According to the analysis's findings, the Bendung, Sekanak, and Buah watershed sub-systems have the greatest priority scales due to their extremely high priority values in comparison to the other watershed sub-systems. The Gandus watershed sub-system, the Gasing watershed sub-system, and the Aur watershed sub-system are the three least important watershed sub-systems that are not yet given priority.